Budgetary inaccuracy of public revenues and expenses of the municipalities of the Immediate Regions of Teófilo Otoni and Águas Formosas - MG between the financial years 2013-2018 (Research, Society and Development, 2021)
The research addresses the budgetary instruments that lead to the identification of budgetary imprecision in the context of Public Financial Management. In this perspective, it is possible to highlight the planning, the public budget, the public revenue and expenditure reports, and the PPA (budgetary multi-year plan), the LDO (bugdet guidelines law) and the LOA (annual budgetary law). The objective is to verify the budgetary inaccuracy between the estimated and the concretized amounts of public revenue collection and expenditure in the municipalities of the Immediate Regions of Teófilo Otoni and Águas Formosas, Minas Gerais state, between the 2013 and 2018 financial years and classify them according to their effectiveness .The data collected from the website of the Court of Auditors of the State of Minas Gerais (TCE-MG) were organized in balanced Panel Data spreadsheets, with a Fixed Effects Model. The scores from the I-Planejamento (a budgetary planning index) and I-Fiscal (a tax collection index) that make up the IEGM-TCEMG (Municipal Management Effectiveness Index by the TCE-MG) were used to classify the dummy variables; and to measure the level of inaccuracy of the municipalities, the classification of the PEFA program was applied. The results showed that, according to the PEFA classification, most municipalities can be considered inaccurate, both in terms of revenue and expenditure, receiving the worst score in the program, conceptualized by the letter D. It was also found that in the econometric estimation, the independent variable “Population” and the dummy variables were significant in explaining this inaccuracy.